2023
DOI: 10.1007/s10459-023-10278-z
|View full text |Cite
|
Sign up to set email alerts
|

Sociomaterial perspective as applied in interprofessional education and collaborative practice: a scoping review

Michael Sy,
Kathryn Lizbeth Siongco,
Roi Charles Pineda
et al.

Abstract: Learning and working together towards better health outcomes today have become more complex requiring an investigation on how interprofessional education (IPE) and interprofessional collaboration (IPC) practices could be sustained and further developed. Through a sociomaterial perspective, we can better understand IPE and IPC practices by foregrounding the material aspect of learning and working together and examining its relationship with humans and their interactions. This article aimed to examine existing l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…However, bringing together professionals from three organizations with different backgrounds added complexity to the situation in at least two ways. First, previous researchers have reported that interprofessional practice can be hampered by power inequality between academic and non-academic staff or between the physicians and other healthcare professionals (Bångsbo et al, 2022 ; Cohen; Konrad et al, 2019 ; Sy et al, 2023 ). Second, professional roles and scopes differ greatly between the healthcare and social fields, calling for more discussion on who professionals are and what they can expect from each other (Ambrose-Miller & Ashcroft, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, bringing together professionals from three organizations with different backgrounds added complexity to the situation in at least two ways. First, previous researchers have reported that interprofessional practice can be hampered by power inequality between academic and non-academic staff or between the physicians and other healthcare professionals (Bångsbo et al, 2022 ; Cohen; Konrad et al, 2019 ; Sy et al, 2023 ). Second, professional roles and scopes differ greatly between the healthcare and social fields, calling for more discussion on who professionals are and what they can expect from each other (Ambrose-Miller & Ashcroft, 2016 ).…”
Section: Discussionmentioning
confidence: 99%